Study of CABAC-based digital video encryption in the H.264/AVC standard - BAO Xian-yu1; JIANG Jian-guo1.2; YUAN Wei1; LI Yuan1 (Tongxin xuebao)
Several candidate domains were analyzed and summarized to apply encryption to the latest video coding standard H.264/AVC,and a novel digital video encryption scheme based on CABAC（context-based adaptive binary arithmetic coding） was proposed.During the CABAC encoding,two kinds of secure encryption operations including RCME（regular coding mode encryption） and BCME（bypass coding mode encryption） were utilized,in order to encrypt residual coefficient codeword,motion vector difference codeword and intra-prediction mode,respectively.The experimental results show that the scheme has significant advantages on security,coding efficiency,and errors robustness.